2021
DOI: 10.1016/j.nmni.2021.100849
|View full text |Cite
|
Sign up to set email alerts
|

Review of potential risk groups for coronavirus disease 2019 (COVID-19)

Abstract: The current pandemic of coronavirus disease 19 (COVID-19) is a global issue caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Studies have revealed that this virus causes poorer consequences and a higher rate of mortality in older adults and those with comorbidities such as cardiovascular disease, hypertension, diabetes, and prolonged respiratory illness. In this review, we discuss in detail the potential risk groups to COVID-19 and outline future recommendations to mitigate the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 91 publications
1
11
0
3
Order By: Relevance
“…The most prevalent comorbidities in our study were hypertension, diabetes, cardiovascular conditions, and asthma. A similar pattern was also found in different studies where hypertension was the most prevalent co-morbidity followed by diabetes, heart diseases, and respiratory illnesses (53)(54)(55). Some other studies revealed the same pattern as mentioned earlier, with hypertension, diabetes, and cardiovascular diseases as the prime co-morbidities (56,57).…”
Section: Discussionsupporting
confidence: 85%
“…The most prevalent comorbidities in our study were hypertension, diabetes, cardiovascular conditions, and asthma. A similar pattern was also found in different studies where hypertension was the most prevalent co-morbidity followed by diabetes, heart diseases, and respiratory illnesses (53)(54)(55). Some other studies revealed the same pattern as mentioned earlier, with hypertension, diabetes, and cardiovascular diseases as the prime co-morbidities (56,57).…”
Section: Discussionsupporting
confidence: 85%
“…We obtained information on a wide range of pre‐existing chronic condition defined as risk factors for severe COVID‐19. 12 The diagnostic codes we used to define these conditions are shown in Table S3 . We required at least two registrations from January 2017 until end of follow‐up to qualify as an existing underlying condition.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained information on a wide range of pre‐existing chronic condition defined as risk factors for severe COVID‐19 12 . The diagnostic codes we used to define these conditions are shown in Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings revealed that 28% of COVID-19 patients had a medical history that included cardiovascular disease and hypertension, type 2 diabetes, respiratory and allergic diseases, autoimmune diseases and endocrine diseases. Similar studies found that hypertension was the most common comorbidity, followed by diabetes, heart disease and respiratory disease (Yang et al, 2020;Ahmad et al, 2021;Naveed et al, 2021). In addition, patients with a serious medical history such as hypertension, heart disease, diabetes mellitus, lung disease and cancer, are also at a greater risk of COVID-19 severity and fatality (Yang et al, 2020;Naveed et al, 2021).…”
Section: Discussionmentioning
confidence: 87%